2018
DOI: 10.3899/jrheum.171375
|View full text |Cite
|
Sign up to set email alerts
|

Flares in Rheumatoid Arthritis Patients with Low Disease Activity: Predictability and Association with Worse Clinical Outcomes

Abstract: Flares occur frequently in RA patients with LDA and are associated with worse disease activity, quality of life, and radiographic progression. Higher baseline HAQ-DI was modestly predictive of flare, while biomarker correlation at the time of flare suggests a noninflammatory component in a majority of events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 34 publications
1
41
3
1
Order By: Relevance
“…In a study to investigate predictors of flare in patients with RA who had LDA and to evaluate the effect of flare on 12-month clinical outcomes, it was found that at time of flare, although DAS28 and its components significantly correlated with MBDA, the correlation coefficients were low, and two-thirds of flares were not associated with a rise in biomarkers 10 .…”
mentioning
confidence: 99%
“…In a study to investigate predictors of flare in patients with RA who had LDA and to evaluate the effect of flare on 12-month clinical outcomes, it was found that at time of flare, although DAS28 and its components significantly correlated with MBDA, the correlation coefficients were low, and two-thirds of flares were not associated with a rise in biomarkers 10 .…”
mentioning
confidence: 99%
“…At each visit, a patient's disease activity was scored following the disease activity (DAS28) score, with 0 indicating no symptoms and 10 representing the greatest disease burden [7]. Besides, CDAI (clinical disease activity index), and SDAI (simplified disease activity index) were applied to RA cohort.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that failure on methotrexate (MTX) and on a following disease modifying anti-rheumatic drugs (DMARD)/biologics treatment leads to an increased flare rate [6]. According to 2018 report, flares are common on a 12-month treatment span for the RA patients with low disease activity, which is not dependent on their biomarker status [7]. Importantly, patients who flared had significantly worse outcomes after a 12-month long treatment [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α overexpression leads to excessive production of many cytokines, such as IL-6 [29,30] . TNF-α and IL-6 are also the two key in ammatory cytokines media in the process of RA sustainable development [31] .…”
Section: Discussionmentioning
confidence: 99%